A expressão no ciberespaço: um voltar-se fenomenologicamente para o diálogo acerca de conteúdos matemáticos - Ferreira, Miliam Juliana Alves [UNESP] (2014)
The improvement of the Technologies of Information and Communication (TIC) resulted in the creation of new ways people communicate and new spaces where this communication takes place. Considering a variety of new spaces, we decided to highlight, on this study, the Cyberspace. On social networks such as Facebook and Orkut, exit many groups and communities focused on discussion and conversation on different topics: from information to entertainment. On this dissertation, we report our experience wi th three virtual communities from Facebook and Orkut. Also, mathematics was the topic of discussion on each of the studied communities. Our goal was to understand, from a phenomenological perspective, how dialogues about mathematics content are possible and how they happen on those social network communities. In order to comprehend these dialogues, we studied the works of Merleau-Ponty. Also, the works of Bicudo and Rosa were extremely important for our understanding of cyberspace. In addition to our theoretical study, we followed two communities on Orkut and one on Facebook. Based on ways which members of these communities expressed themselves, we tried to analyze how dialogues about mathematics occur and what they reveal about math. The analyzes of our data, designed on phenomenological manner, allowed us to create four open-categories: listen the other, expression by speech, expression by image, and expression by the use of mathematical language. The interpretation of these categories presented to us how individuals talked about math on the cyberspace. We realized that the 'listen the other' is a started for communication. Complementarily, we noticed the intentional desire of individuals to be with others members of the community. On the dialogue, the 'be-with' shows itself by the speech. On the cyberspace, the 'be-with' is represented by the written text, image that speaks and by the oral expression